The Effect of Ethanol Addition to Gasoline Fuel: A Comprehensive Analysis of Performance, Emissions, and Material Compatibility Based on Literature Studies - Pardomuan Robinson Sihombing (CV Pena Jaya Pers, 2026)
Background: Using bioethanol as an oxygenate additive in gasoline shows an increasing trend driven by the need for renewable fuels and efforts to mitigate exhaust emissions. Purpose: This study aims to conduct a critical and comprehensive synthesis of the positive and negative impacts of ethanol addition, focusing on engine performance, exhaust emissions, and material compatibility. Design/methodology/approach: The method used was a systematic literature review of primary scientific journals indexed by Scopus and SINTA. Findings: The analysis results show a dualism of impacts: on the one hand, adding ethanol consistently increases engine torque and power and significantly reduces carbon monoxide (CO) and hydrocarbon (HC) emissions. On the other hand, this is offset by the potential for increased fuel consumption due to the lower energy density of ethanol, ambiguous effects on nitrogen oxide (NOx) emissions, and the emergence of serious challenges related to corrosion of metal components and degradation of elastomer materials. Implication: These findings imply that adopting ethanol blends requires a holistic approach, including engine design optimization and improved material specifications in fuel systems to ensure long-term durability and safety. Paper type: Literature review